STRATEGI TELEVISI LOKAL, MEMBENTUK OPINI PEMILIH PEMULA DENGAN CERDAS - Pamungkas, Hery (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2015)
Abstract:The problem of this research starting from lack of beginner voter participation in using their voting rights, as well as the still lack of government support in the socialization of democratic education for voters. The purpose of this study to determine how effective the approach of local TV (TVKU Semarang) in cooperation with the Commission (KPU of Semarang) through the general elections program OSIS (Pemilos) in improving the level of awareness and understanding of political actualization of the students as voters. This research uses descriptive quantitative research methods. The population of this study were 100 high school students in the city of Semarang were aged 17-21 years and has attended educational programs democracy